2021
DOI: 10.1108/jcms-03-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Equity crowdfunding and financial literacy of individual investors in Japan

Abstract: PurposeThis study aims to fill the gap in previous research that focuses on the superficial aspects of equity crowdfunding (ECF) campaigns and financial practices by examining financial literacy aspects, such as due diligence and valuation, in terms of factors that influence Japanese individual investors' investments in ECF.Design/methodology/approachThe status of information disclosure in ECF campaigns is checked. In addition, the feasibility of the initial due diligence and valuation using this information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…This type of ECF market is unique in Japan when compared to the Yoshiaki Nose, Chie Hosomi / rest of the world. We have previously indicated that Japanese individual investors may not distinguish between common stock and stock acquisition rights and we emphasized the lack of financial literacy among individual investors (Fujii et al, 2021). However, a comprehensive empirical analysis that accounts for more variables remains an issue, which is addressed in this study.…”
Section: Issues In Prior Researchmentioning
confidence: 92%
See 3 more Smart Citations
“…This type of ECF market is unique in Japan when compared to the Yoshiaki Nose, Chie Hosomi / rest of the world. We have previously indicated that Japanese individual investors may not distinguish between common stock and stock acquisition rights and we emphasized the lack of financial literacy among individual investors (Fujii et al, 2021). However, a comprehensive empirical analysis that accounts for more variables remains an issue, which is addressed in this study.…”
Section: Issues In Prior Researchmentioning
confidence: 92%
“…The Lack of Financial Literacy Hypothesis assumes that individual investors are either unable or unwilling to comprehend the information and signals provided by start-ups and platforms and therefore invest "without understanding" and "somehow." Financial literacy in this context does not refer to a superficial understanding of the information disclosed in ECF, but rather determines whether or not they can perform "due diligence" and "valuation" (Fujii et al, 2021), which professional investors, such as venture capitalists, take for granted.…”
Section: Lack Of Financial Literacy Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Investor harus dapat mengetahui finansial, Fujii et al (2021) mengatakan bahwa investor yang mengerti finansial dapat memperkirakan nilai pasar yang diharapkan dari saham biasa. Mengerti finansial atau mengerti keuangan penting dalam kegiatan investasi, Simpulan Disney et al (2015), mengerti keuangan menurunkan kemungkinan individu mencari bantuan dari konselor kredit sekitar 60%.…”
Section: Pendahuluanunclassified